The impact of family support on metabolic control in patients with type 2 diabetes - Matej-Butrym, Agata; Butrym, Marek; Jaroszyński, Andrzej (Polish Journal of Public Health, 2012)
Introduction. Conscientious compliance with medical prescriptions is a key element of the therapeutic process in patients with type 2 diabetes.Aim. The aim of this study was to assess to what extent and with what involvement the family members of patients with type 2 diabetes participate in selected activities related to the treatment of diabetes and whether it has any impact on metabolic control.Material and methods. A total of 136 patients with type 2 diabetes were examined. The research was conducted by means of physical examination, laboratory tests (glycosylated hemoglobin A1c, fasting glucose and lipid profile) and questionnaire survey assessing family members’ participation in selected aspects of the therapeutic procedures in patients with diabetes. Results. The results of the study indicate that the extent of support and family involvement in helping the patient with type 2 diabetes are not satisfactory, and the received support is not reflected in better glycaemic control. The study showed a significant negligence not only in participation of family members but also of the patients themselves in diabetes education.Conclusions. The results indicate the need to intensify the education of the families of patients suffering from type 2 diabetes, so that they provide greater support to the sick, particularly in terms of compliance with dietary recommendations.